Influence of a defoaming agent – simethicone – on endoscope cleaning and disinfection: Prospective real-world study - Huang, Juanjuan; Ling, Tingsheng; Zhang, Junlin; Wei, Lianzhen; Chen, Lei; Cao, Huiwen; Wang, Lei; Liu, Yitong; Wen, Dongkun; Ren, Danrui; Li, Yang (Endoscopy International Open, 2025)
Simethicone has been extensively utilized in endoscopy examinations and therapies; however, consensus regarding its impact on endoscopy cleaning is still lacking. The aim of this study was to assess impact of simethicone use during endoscopic examination on efficacy of endoscope cleaning.This was a prospective real-world study that involved use of varying concentrations of simethicone in the endoscope biopsy channel and auxiliary water channel.All simethicone residual amounts and adenosine triphosphate (ATP) values were analyzed every month for 1 year. Use of 1% and 2% concentrations of simethicone generally resulted in variations in residual simethicone levels between the two channels. There was no significant alteration in ATP values in any concentration between the two channels. However, there was a significant difference in ATP values between the two channels at the concentration of 1% simethicone. After 1 year of usage, suspected adherent was observed in the 2% simethicone group, whereas no crystals were detected adhering to the biopsy channel walls in the 1% group or the control group. Sensitivity analysis suggested that the study results did not differ between the gastroscopy and colonoscopy subgroups.Simethicone may remain in the biopsy and water infusion channels, regardless of whether it is used or not. It is recommended to utilize a simethicone concentration of 1% or less when administering it through the biopsy or auxiliary water channels of the endoscope.
Keywords: Quality and logistical aspects; Quality management; Preparation